2017
DOI: 10.1053/j.seminoncol.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study demonstrating metabolic and anti-proliferative effects of in vivo anti-oxidant supplementation with N-Acetylcysteine in Breast Cancer

Abstract: Background High oxidative stress as defined by hydroxyl and peroxyl activity is often found in the stroma of human breast cancers. Oxidative stress induces stromal catabolism, which promotes cancer aggressiveness. Stromal cells exposed to oxidative stress release catabolites such as lactate, which are up-taken by cancer cells to support mitochondrial oxidative phosphorylation. The transfer of catabolites between stromal and cancer cells leads to metabolic heterogeneity between these cells and increased cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Great attention has been paid to the anti-tumor effects of NAC. Recently, Monti et al (32) reported that NAC as a single agent reduced MCT4 stromal expression, which is a marker of glycolysis in breast cancer with reduced carcinoma cell proliferation in a clinical trial. However, other previous studies confirmed NAC inhibited anti-tumor effect of some chemical agents isolated from the plant, such as britannin, (33) Umbilicaria esculenta, (34) and cryptotanshinone.…”
Section: Discussionmentioning
confidence: 99%
“…Great attention has been paid to the anti-tumor effects of NAC. Recently, Monti et al (32) reported that NAC as a single agent reduced MCT4 stromal expression, which is a marker of glycolysis in breast cancer with reduced carcinoma cell proliferation in a clinical trial. However, other previous studies confirmed NAC inhibited anti-tumor effect of some chemical agents isolated from the plant, such as britannin, (33) Umbilicaria esculenta, (34) and cryptotanshinone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Monti et al demonstrated in a clinical trial that NAC, reducing MCT-4 expression in the tumour stroma of cancer patients, decreases carcinoma cell proliferation rates in women with stages 0 and I breast cancer. This pilot clinical trial showed NAC effectiveness and safety in breast cancer treatment [ 91 ]. Moreover, NAC in combination with topotecan underwent a phase 2 clinical trial in ovarian cancer patients, based on their role in the regulation of Cav-1, MCT-4, and HIF-1 α expression [ 20 ].…”
Section: Therapeutic Responses To Cafs Metabolic Reprogrammingmentioning
confidence: 99%
“…In the same clinical trial, metformin was shown to induce CAV1 expression in CAFs, preventing the metabolic coupling between stromal and cancer cells ( 240 , 241 ). Another example of effective anti-metabolic cancer therapies is the use of N-acetyl cysteine (NAC), whose antioxidant potential reduced both the proliferation of cancer cells and the expression of the metabolic coupling monocarboxylate transporter 4 (MCT4) in stromal cells in a clinical trial in breast cancer ( 242 ). In summary, inhibiting oxidative metabolism or altering the redox state of tumors appear as promising approaches for the treatment of cancer.…”
Section: Targeting the Tumor Metabolic Ecosystemmentioning
confidence: 99%